PENGGUNAAN METODE PROBLEM SOLVING DAN PENGARUHNYAA PADA HASIL BELAJAR SISWA PPKn DI SMP ISLAM AL-ANWAR GULUK - GULUK SUMENEP - Abd Basith (JURNAL SETIA PANCASILA, 2021)
This study aims to, First, to determine the effect of the application of problem solving methods on student Civics learning outcomes at Al-Anwar Guluk Islamic Middle School - GulukSumenep. Second, to find out the magnitude of the effect of the application of problem solving methods on student Civics learning outcomes at Al-Anwar Guluk Islamic Middle School - GulukSumenep. This study uses a quantitative approach, because this research deals with numbers. The population in this study were all students as many as 59 students. Given the total population is less than 100, the researchers took all of the population, namely as many as 59 which are known as population research. The instruments used in data collection are questionnaires, interviews, observation and documentation. The data collection lasted 40 days from January 10 to February 20, 2020. The data analysis technique used was statistical analysis using the product moment correlation formula. The results show that: First, there is an effect of the application of the problem solving method on student Civics learning outcomes at Al-Anwar Guluk Islamic Junior High School - GulukSumenep, this is evident from the results of data analysis, that the r work value of 0.690 is greater than the r value of the product moment table. , where at db = 59 in the 5% confidence interval the r value of the product moment table is 0.266 and in the 1% confidence interval the r value of the product moment table is 0.345. Second, the application of the problem solving method has a sufficient effect on student civics learning outcomes at Islamic Junior High School Al-Anwar Guluk - GulukSumenep, because the r work value of 0.690 is in the series of numbers from 0.600 to 0.800 high interpretation. After it is known that the application of problem solving methods has a significant effect on student motivation, it is advisable to apply the method of problem solving methods, so that student learning motivation increases.